Praktek Medical Aesthetic Tourism Dalam Perlindungan Hukum Warga Negara - Linda Wianti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Medical Aesthetic Tourism shows significant growth in recent years. A study on its law protection should be conducted more in-depth to enable this trend to give the feeling of secure to its actors. This article aimed to study and to analyze Law Protection of Medical Aesthetic Tourism. This study was a doctrinal research referring to primary, secondary and tertiary data sources, with interactive technique of analyzing data. The result showed the Law Protection of Medical Aesthetic Tourism related to medical service standardization, product security standard, insurance, medical risk litigation during action and treatment. This law protection is studied from the perspective of Pancasila and Republic of Indonesia’s 1945 Constitution, and related international law. This narrative literature review focused on the problem of law protection for the tourists getting Medical Aesthetic Tourism treatment abroad.